Exploring consumer behavior at slow food festivals in rural destinations. - Adeyinka-Ojo, Samuel Folorunso; Khoo-Lattimore, C. (Taylor & Francis Group, 2017)
This text explores and critically examines current debates, critical reflections of contemporary ideas, controversies and pertinent queries relating to the rapidly expanding discipline of consumer behaviour in hospitality and tourism.